IMPLEMENTATION OF PANCASILA IN THE DIGITAL ERA - Dewi, Aisyah (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2024)
Pancasila as the national symbol of Indonesia continues to be relevant in facing the challenges of the digital era. This article discusses how the teachings of Pancasila are applied in the context of increasingly dominant information and communication technology. Pancasila contains rules for the development of digital technology and people's behavior in cyberspace, in harmony with the development of just and civilized prosperity, Indonesian Unity, Democracy Led by Wisdom in Deliberation and Representation, and Social Justice for All Indonesian People. Pancasila emphasizes the importance of human dignity, equality and justice, all of which are relevant in the context of the digitalization era. In addition, this article discusses issues that need attention in the digital era, such as the need to respect religious freedom in using technology, dealing with disinformation, increasing digital literacy, and ensuring more public participation in making various decisions. In the current era of digitalization, it is very important to ensure that digital technology provides benefits for social, national and state life by containing Pancasila values ??which are the basis of the Indonesian nation state.